"Coping in the Time of Crisis": A Study on College Students' Mental Health and Coping Mechanisms amidst the COVID-19 Pandemic. - Amir Bhochhibhoya; Liz McDowell; Sayward Harrison (New Prairie Press, 2024)
The sudden closure of colleges and universities, among other challenges, disrupted higher education across US states during the subsequent waves of the COVID-19 pandemic, significantly impacting the mental health of college students. The study was designed to comprehend the major stressors that college students encountered during the COVID-19 pandemic and the strategies they employed to cope with these stressors. The participants included undergraduate students from a small rural public university in the Southeast region of the US. A survey comprising 35 items to evaluate the effects of COVID-19 on mental health and coping mechanisms was employed. The study included 170 student participants. Descriptive statistics were used to summarize quantitative data and a thematic qualitative analytic approach was employed for qualitative data. The majority of the participants reported increased stress and negative emotions, and also faced financial hardships. Participants also reported receiving social support from friends and family. The study found that students predominantly used social and entertainment-based coping mechanisms, while mindfulness-based exercises were the least utilized coping strategies. College students who experienced increased stress during the COVID-19 pandemic are more likely to develop mental and behavioral health disorders, experience academic challenges, and have a lower quality of life. Even though the pandemic is over, continued proactive support and well-designed interventions are needed to address the lingering effects of the pandemic and support their overall well- being.